Advanced small cell lung cancer with severe hyponatremia: a case report and literature review - Li, Xu; Xu, Tongtong; Jian, Xian (Frontiers in Oncology, 2025)
Small cell lung cancer (SCLC) is a rare pathological type of lung cancer, frequently associated with neuroendocrine symptoms such as hyponatremia. This article presents a case involving a 59-year-old male patient admitted to the hospital with neurological symptoms and severe hyponatremia. He was diagnosed with SCLC accompanied by syndrome of inappropriate antidiuretic hormone secretion (SIADH) upon admission. Following oral and intravenous sodium supplementation, along with the administration of tolvaptan, the patient’s serum sodium levels increased. However, upon initiating chemotherapy, the patient’s hyponatremia worsened, leading to seizures and the need for ventilator support therapy. Despite normalization of serum sodium levels, the patient’s symptoms did not improve. Ultimately, due to the severity of the patient’s condition, the family elected to discontinue further medical intervention and proceeded with hospital discharge. Thus, in clinical practice, when encountering unexplained refractory hyponatremia with lung lesions, clinicians should consider the possibility of lung cancer with SIADH to ensure timely and precise treatment.